Comparison of F-18 FDG-PET/CT and Tc-99m MIBI in the preoperative evaluation of cold thyroid nodules in the same patient group - ERDOĞAN, EZGİ BAŞAK; Sağer, Sait; Vatankulu, Betül; ERDOĞAN, EZGİ BAŞAK; Mut, Sanem; Teksöz, S; Öztürk, T; Sönmezoğlu, Kerim; Kanmaz, Bedii (My University, 2015)
Recent studies have reported that standardized uptake values of FDG-PET imaging might predict malignant thyroid nodules and can be used in the preoperative evaluation of thyroid lesions. The aim of our study was to evaluate FDG-PET imaging in patients with cold thyroid nodules and to compare the imaging findings with Tc-99m MIBI scans and with post-op histopathology results. Twenty-three patients (18F, 5M) with 24 nodules that were suspicious in ultrasound and cold in Tc-99m pertechnetate scan, were included in the study. Each nodule underwent sonographically guided fine-needle aspiration biopsy. FDG-PET and MIBI scans were performed with an interval of 3-5 days. All patients underwent thyroidectomy and their FDG-PET, and MIBI thyroid scan results were compared with post-thyroidectomy pathology results. Post-op histopathology results found 7 malignant and 17 benign nodules. Six of the seven malignant nodules had increased uptake, which were positive for malignancy in both PET and MIBI scans. Each imaging method used different radiopharmaceuticals but showed one false-negative result in two different patients. FDG-PET produced false positives in eight nodules and MIBI scans found false positives in four nodules. FDG-PET imaging and MIBI scan showed the same sensitivity in malignant nodule evaluation, but their specificity differed. As a result, we suggest that FDG-PET imaging is not superior to MIBI scanning in differentiating malignant from benign thyroid nodules. MIBI imaging should be the first choice in the preoperative evaluation of patients with cold thyroid nodules as an adjunct procedure to FNAB because of its low cost and availability. This imaging technique can be used routinely in patients who are reluctant to undergo FNAB.